The Maize Corngrass1 miRNA-Regulated Developmental Alterations Are Restored by a Bacterial ADP-Glucose Pyrophosphorylase in Transgenic Tobacco - Ayalew Ligaba-Osena; Kay DiMarco; Tom L. Richard; Bertrand Hankoua (International Journal of Genomics)
Crop-based bioethanol has raised concerns about competition with food and feed supplies, and technologies for second- and third-generation biofuels are still under development. Alternative feedstocks could fill this gap if they can be converted to biofuels using current sugar- or starch-to-ethanol technologies. The aim of this study was to enhance carbohydrate accumulation in transgenic Nicotiana benthamiana by simultaneously expressing the maize Corngrass1 miRNA (Cg1) and E. coli ADP-glucose pyrophosphorylase (glgC), both of which have been reported to enhance carbohydrate accumulation in planta. Our findings revealed that expression of Cg1 alone increased shoot branching, delayed flowering, reduced flower organ size, and induced loss of fertility. These changes were fully restored by coexpressing Escherichia coli glgC. The transcript level of miRNA156 target SQUAMOSA promoter binding-like (SPL) transcription factors was suppressed severely in Cg1-expressing lines as compared to the wild type. Expression of glgC alone or in combination with Cg1 enhanced biomass yield and total sugar content per plant, suggesting the potential of these genes in improving economically important biofuel feedstocks. A possible mechanism of the Cg1 phenotype is discussed. However, a more detailed study including genome-wide transcriptome and metabolic analysis is needed to determine the underlying genetic elements and pathways regulating the observed developmental and metabolic changes.